Single-crystal ternary positive electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202611053824.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]本发明提供一种单晶三元正极材料及其制备方法和应用,可以解决现有技术中改性剂的分散性差、导致改性效果难以充分发挥,无法显著提升电化学性能的问题
本发明S1步骤通过三元前驱体材料、锂源与添加剂的混合及首次烧结,实现锂与前驱体的固相反应,完成单晶核的初步形成与元素均匀分布,为后续材料的晶型生长奠定基础,保障材料基础结构与电化学性能的雏形构建;S2步骤将一次烧结产物与硼酸、改性羟基氧化钴在有机溶剂中分散后进行二次烧结,一方面硼酸形成的玻璃态包覆层能够有效隔离材料与电解液,抑制副反应的发生,提高材料的界面稳定性;另一方面改性羟基氧化钴能调控单晶形貌与晶粒生长,调控单晶颗粒的形貌与晶粒尺寸,提升结晶度与结构完整性,提升单晶结晶度与结构完整性,减少晶格畸变与缺陷,降低锂离子传输的晶格阻抗,有效提升材料的离子电导率与倍率性能,二者协同作用可优化材料的晶体结构完整性、界面稳定性与离子传输性能,最终获得电化学性能优异、循环稳定性与安全性俱佳的单晶三元正极材料。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of energy storage materials technology, and in particular to a single-crystal ternary cathode material, its preparation method, and its application. Background Technology
[0002] With the widespread application of lithium batteries in electric vehicles, energy storage systems, and other fields, higher requirements have been placed on their energy density, cycle stability, and safety. Ternary cathode materials have attracted much attention due to their high energy density, with single-crystal ternary cathode materials exhibiting better structural stability and cycle performance compared to polycrystalline materials. However, current single-crystal ternary cathode materials still face some challenges in practical applications. For example, their unstable surface structure makes them prone to side reactions with the electrolyte during charge and discharge, leading to a decrease in cycle performance and rate capability. Furthermore, the electronic and ionic conductivity of these materials needs improvement, limiting their application in high-power fields. While existing surface modification methods can improve material performance to some extent, they suffer from unsatisfactory modification effects and complex preparation processes, making it difficult to meet the demands of large-scale industrial production. Therefore, developing a preparation method that can effectively improve the performance of single-crystal ternary cathode materials is of significant practical importance.
[0003] Currently, the industry mainly uses doping and surface modification technologies to reduce the free lithium content and DC internal resistance of products, thereby improving the cycling stability of single-crystal ternary materials under high temperature, high nickel, and high pressure environments. However, in existing technologies, unreasonable selection and ratio of dopants or coating agents often result in poor cycling and rate performance under high voltage. Furthermore, traditional surface modification methods often employ single modifiers or simple composite modifications, leading to problems such as unsatisfactory modification effects, weak bonding between modified components and the matrix, and easy detachment of the coating layer. Moreover, the preparation process is complex and costly, making it difficult to meet the needs of large-scale industrial production. In addition, during surface modification, the poor dispersibility of the modifier hinders the full realization of the modification effect, failing to significantly improve electrochemical performance. Summary of the Invention
[0004] This invention provides a single-crystal ternary cathode material, its preparation method, and its application, which can solve the problem in the prior art where the modifier has poor dispersibility, making it difficult to fully exert the modification effect and significantly improve electrochemical performance.
[0005] The objective of this invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a method for preparing a single-crystal ternary cathode material, comprising the following steps: S1. The ternary precursor material, lithium source and additives are mixed and sintered for the first time to obtain the first sintered product. S2. The primary sintering product, along with boric acid and modified cobalt hydroxyl oxide, are added to an organic solvent, mixed, ultrasonically dispersed, and then sintered a second time to obtain a single-crystal ternary cathode material.
[0006] Further, in step S1, the molar ratio of Li ions to ternary precursor material is (1.02-1.06):1; the molar ratio of additive to ternary precursor material is (0.02-0.05):1.
[0007] Furthermore, in step S1, the ternary precursor material is Ni. 0.65 Co 0.15 Mn 0.20 (OH) 2; The lithium source is Li2CO3.
[0008] Further, in step S1, the additive includes any one or more of ZrO2, Al2O3 and Y2O3.
[0009] Further, in step S1, the first sintering is first heated to 500-600℃ at 3-5℃ / min and sintered at a constant temperature for 2 hours; then heated to 900-950℃ at 2.5-3℃ / min and sintered at a constant temperature for 8-10 hours.
[0010] Further, in step S2, the amount of boric acid used accounts for 0.05%-0.1% of the mass of the primary sintering product; the amount of modified cobalt hydroxyoxide used accounts for 0.3%-0.5% of the mass of the primary sintering product.
[0011] Further, in step S2, the organic solvent is an aqueous ethanol solution with a volume fraction of 90%, and the mass ratio of the organic solvent to the primary sintering product is 2:3.
[0012] Further, in step S2, the method for preparing the modified cobalt hydroxyoxide is as follows: Cobalt hydroxyoxide was added to an aqueous ethanol solution, ultrasonically dispersed, a modified silane coupling agent was added, the mixture was stirred, washed, and dried to obtain modified cobalt hydroxyoxide.
[0013] Furthermore, the ratio of cobalt hydroxyoxide, aqueous ethanol solution, and modified silane coupling agent is 1g:8-10mL:0.05-0.1g; the volume fraction of the aqueous ethanol solution is 90%.
[0014] Furthermore, the stirring reaction time is 1-2 hours.
[0015] Furthermore, the particle size of the cobalt hydroxyoxide is 10-40 nm.
[0016] Furthermore, the preparation method of the modified silane coupling agent is as follows: Glycidyl ether was added to a mixture of γ-isocyanate-propyltrimethoxysilane and dibutyltin dilaurate, and the mixture was heated and stirred to obtain a modified silane coupling agent.
[0017] Furthermore, the mass ratio of glycidyl ether, γ-isocyanate-propyltrimethoxysilane, and dibutyltin dilaurate is 7.4:21.9:0.0295.
[0018] Furthermore, the heating and stirring reaction is carried out at a temperature of 50-60°C for 1-2 hours.
[0019] Furthermore, in step S2, the secondary sintering is carried out at a rate of 3°C / min to 300°C-500°C, and then sintered at a constant temperature for 8-10 hours.
[0020] Secondly, the present invention provides a single-crystal ternary cathode material, which is prepared by any one of the preparation methods described above.
[0021] The beneficial effects of this invention are: In step S1 of this invention, the solid-state reaction between lithium and the precursor is achieved through the mixing and initial sintering of ternary precursor materials, lithium source, and additives. This completes the initial formation of single crystal nuclei and uniform elemental distribution, laying the foundation for subsequent crystal growth and ensuring the initial construction of the material's basic structure and electrochemical performance. In step S2, the product from the first sintering is dispersed in an organic solvent with boric acid and modified cobalt hydroxyoxide, followed by a second sintering. On the one hand, the glassy coating layer formed by boric acid can effectively isolate the material from the electrolyte, suppress side reactions, and improve the interfacial stability of the material. On the other hand, modified cobalt hydroxyoxide can regulate the morphology and grain growth of single crystals, improve crystallinity and structural integrity, reduce lattice distortion and defects, lower the lattice impedance of lithium-ion transport, and effectively improve the ionic conductivity and rate performance of the material. The synergistic effect of these two steps optimizes the crystal structure integrity, interfacial stability, and ion transport performance of the material, ultimately obtaining a single-crystal ternary cathode material with excellent electrochemical performance, cycle stability, and safety.
[0022] In this method, modified cobalt hydroxyl oxide is creatively used, which can significantly improve the electrochemical performance of ternary cathode materials, as detailed below: 1. Modified cobalt hydroxyoxide has better dispersibility. It is uniformly dispersed on the material surface and at grain boundaries, filling grain boundary defects and reducing interfacial resistance to lithium-ion transport.
[0023] 2. The modified cobalt hydroxyl oxide surface contains epoxy and urethane groups. The epoxy groups on the modified cobalt hydroxyl oxide surface can undergo a ring-opening addition reaction with boric acid, significantly enhancing the binding force between the two coating components. This ensures the integrity of the coating layer during long-term charge-discharge processes, significantly improving cycle stability. Simultaneously, the carbonyl oxygen and amino nitrogen in the urethane groups can act as dual coordination sites to form a stable chelate structure with lithium ions, constructing a low-impedance lithium-ion fast transport channel at the interface and reducing interfacial polarization. The synergistic effect of these two components ensures the long-term stability of the interfacial structure through chemical bonding and optimizes lithium-ion migration kinetics through coordination, thereby achieving a simultaneous improvement in cycle life and rate performance. Detailed Implementation
[0024] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below.
[0025] In a first aspect, the present invention provides a method for preparing a single-crystal ternary cathode material, comprising the following steps: S1. The ternary precursor material, lithium source and additives are mixed and sintered for the first time to obtain the first sintered product. In the above steps, the ternary precursor material, lithium source and additives are mixed and then sintered at high temperature. Solid-phase lithiation reaction and element doping reaction occur in the system. The lithium ions provided by the lithium source undergo lattice substitution and diffusion with the metal elements in the precursor, completing the initial single crystal nucleation and crystal growth. The additives are doped into the lattice or grain boundary, regulating the crystal structure and grain morphology, laying the foundation for the formation of single crystal ternary materials.
[0026] S2. The primary sintering product, along with boric acid and modified cobalt hydroxyl oxide, are added to an organic solvent, mixed, ultrasonically dispersed, and then sintered a second time to obtain a single-crystal ternary cathode material.
[0027] In the above steps, the primary sintering product, boric acid, and modified cobalt hydroxyl oxide are ultrasonically dispersed in an organic solvent and then subjected to secondary sintering. On the one hand, boric acid reacts with the residual alkali on the material surface to form a glassy coating layer, and the epoxy groups on the surface of the modified cobalt hydroxyl oxide undergo a ring-opening addition reaction with boric acid, strengthening the interfacial bonding force of the coating layer. On the other hand, the modified cobalt hydroxyl oxide regulates the growth of single-crystal grains, and the polar groups on its surface coordinate with lithium ions to construct low-impedance ion transport channels, ultimately achieving structural optimization and performance improvement of the single-crystal ternary cathode material.
[0028] In some embodiments, in step S1, the molar ratio of Li ions to the ternary precursor material is (1.02-1.06):1; the molar ratio of the additive to the ternary precursor material is (0.02-0.05):1. Under this ratio, the precise molar ratio of lithium ions to the ternary precursor provides sufficient lithium source for the material, ensuring the uniformity of ion doping in the lattice and the integrity of the crystal structure. A specific proportion of additives can regulate grain growth, inhibit impurity phase formation, and optimize material interface characteristics, synergistically improving the electrochemical performance of single-crystal ternary materials. An excessively high lithium ion ratio can easily lead to impurity phases and abnormal grain growth during material sintering, causing lattice distortion and reducing ionic conductivity. An excessive additive ratio will form dense byproducts on the material surface, hindering ion transport channels and exacerbating interface impedance, ultimately leading to a deterioration in the material's cycle stability and rate performance. Insufficient lithium-ion ratio will lead to an increase in lattice defects and the absence of active sites, directly reducing the specific capacity and lithium insertion / extraction efficiency of the material; if the additive ratio is too low, it will be difficult to effectively control grain growth, suppress the generation of impurity phases, and the structural stability and electrochemical performance of the material cannot be optimized.
[0029] In some embodiments, in step S1, the ternary precursor material is Ni. 0.65 Co 0.15 Mn 0.20 (OH)2; the lithium source is Li2CO3. This process enables highly efficient solid-phase lithiation, yielding a single-crystal ternary cathode material with high crystallinity and stable structure, achieving both high specific capacity and excellent electrochemical cycling performance.
[0030] In some embodiments, in step S1, the additive includes any one or more of ZrO2, Al2O3, and Y2O3. This can effectively regulate the crystal structure of single-crystal materials, inhibit grain growth, and improve the structural stability and cycling performance of the materials.
[0031] In some embodiments, in step S1, the first sintering involves first heating to 500-600℃ at a rate of 3-5℃ / min and sintering at that temperature for 2 hours; then heating to 900-950℃ at a rate of 2.5-3℃ / min and sintering at that temperature for 8-10 hours. This segmented heating sintering process effectively promotes phase transformation and uniform grain growth, optimizes crystal structure density, reduces defects and impurity phase formation, and improves the structural stability and overall performance of the product. Excessive heating rate can lead to significant thermal stress within the material, causing grain cracking, increased porosity, and a loose structure, while also easily resulting in impurity phase formation and reduced product performance. Conversely, excessively slow heating rates prolong the sintering cycle, increase energy consumption, and may also lead to excessive grain growth and decreased density, affecting the material's performance. If the sintering temperature is too low or the holding time is insufficient, it will lead to incomplete phase transformation, insufficient crystal structure development, and high porosity, thereby reducing the core indicators of the material such as mechanical properties, electrical conductivity / thermal conductivity, etc. If the sintering temperature is too high or the holding time is too long, it will cause problems such as abnormal grain growth, excessive material densification, and grain boundary segregation. At the same time, it will increase energy consumption and production costs, and may also damage the functional structure of the material and reduce its stability in use.
[0032] In some embodiments, in step S2, the amount of boric acid used accounts for 0.05%-0.1% of the mass of the primary sintering product; the amount of modified cobalt hydroxyoxide used accounts for 0.3%-0.5% of the mass of the primary sintering product. This can achieve a synergistic modification effect. Excessive use can easily lead to problems such as increased impurity phases and agglomeration, while insufficient use will result in insufficient modification and failure to achieve the expected performance optimization goal.
[0033] In some embodiments, in step S2, the organic solvent is a 90% (v / v) aqueous ethanol solution, and the mass ratio of the organic solvent to the primary sintering product is 2:3. This ratio and dosage can achieve efficient dispersion modification and optimize the material structure and properties.
[0034] In some embodiments, the method for preparing the modified cobalt hydroxyl oxide in step S2 is as follows: Cobalt hydroxyoxide was added to an aqueous ethanol solution, ultrasonically dispersed, a modified silane coupling agent was added, the mixture was stirred, washed, and dried to obtain modified cobalt hydroxyoxide.
[0035] In the above steps, cobalt hydroxyl oxide is ultrasonically treated in an ethanol-water solution to form a uniform suspension. The modified silane coupling agent undergoes a chemical bonding reaction with the hydroxyl groups on the surface of cobalt hydroxyl oxide through its functional groups, thereby achieving surface modification of inorganic particles by organic functional groups. The dispersibility of the modified cobalt hydroxyl oxide is significantly improved, and agglomeration is effectively suppressed. At the same time, the surface organic functional groups improve its interfacial compatibility, enhance the dispersion stability and binding force of the material in the composite system, and ultimately optimize the overall structure and functional performance of the material.
[0036] In some embodiments, the ratio of cobalt hydroxyoxide, aqueous ethanol solution, and modified silane coupling agent is 1g:8-10mL:0.05-0.1g; the volume fraction of the aqueous ethanol solution is 90%. Insufficient coupling agent will not achieve adequate surface coating and modification, making it difficult to improve dispersibility and interfacial compatibility. Excessive coupling agent will form an excessive coating layer on the particle surface, leading to decreased material density, reduced interfacial bonding, increased side reactions, and decreased product performance. Insufficient aqueous ethanol solution will reduce the wetting effect of the dispersion medium on cobalt hydroxyoxide, exacerbating particle agglomeration. Excessive ethanol solution will dilute the concentration of each component in the system, affecting the efficiency of the modification reaction and the binding stability of the product.
[0037] In some embodiments, the stirring reaction time is 1-2 hours. This duration and particle size ensure sufficient reaction and stable interfacial bonding. Excessive time can lead to product structure damage and increased energy consumption, while insufficient time results in incomplete reaction and poor modification effect.
[0038] In some embodiments, the cobalt hydroxyoxide has a particle size of 10-40 nm. If the particle size is too large, it is prone to uneven dispersion and weakened interfacial interaction; if the particle size is too small, it is prone to agglomeration and increased processing difficulty.
[0039] In some embodiments, the modified silane coupling agent is prepared by: Glycidyl ether was added to a mixture of γ-isocyanate-propyltrimethoxysilane and dibutyltin dilaurate, and the mixture was heated and stirred to obtain a modified silane coupling agent.
[0040] In the above steps, the isocyanate group (-NCO) in γ-isocyanate-propyltrimethoxysilane undergoes nucleophilic addition with the hydroxyl group (-OH) in glycidyl ether under the catalysis of dibutyltin dilaurate to generate a carbamate bond (-NH-COO-). At the same time, the epoxy group in the glycidyl ether molecule is completely retained, and finally a silane coupling agent containing both epoxy and carbamate groups is obtained.
[0041] In some embodiments, the mass ratio of glycidyl ether, γ-isocyanate-propyltrimethoxysilane, and dibutyltin dilaurate is 7.4:21.9:0.0295. This mass ratio ensures that glycidyl ether reacts efficiently with γ-isocyanate-propyltrimethoxysilane to generate the target modified silane coupling agent, and that dibutyltin dilaurate has moderate catalytic activity, resulting in a high grafting rate and good dispersibility of the coupling agent. Excessive catalyst dosage can easily lead to side reactions, darken the product color, and affect subsequent application performance; insufficient dosage results in a slow reaction rate, incomplete reaction, and difficulty in obtaining a sufficient amount of active functional groups. An imbalance in the ratio of glycidyl ether or silane monomers will lead to a single functional group in the product, insufficient modification effect, and inability to effectively achieve organic modification and performance optimization of the cobalt hydroxyl oxide surface.
[0042] In some embodiments, the heating and stirring reaction is carried out at a temperature of 50-60°C for 1-2 hours. This ensures that the coupling reaction is complete and controllable. Excessive temperature or time can easily lead to increased side reactions, discoloration or decomposition of the product, while excessively low temperature or short time will result in incomplete reaction and insufficient modification effect.
[0043] In some embodiments, in step S2, the secondary sintering involves heating to 300℃-500℃ at a rate of 3℃ / min and then isothermal sintering for 8-10 hours. Precise control of the heating rate, sintering temperature, and time can achieve homogenized material structure modification and improve interfacial bonding and stability. Excessive temperature or sintering time can lead to coarse grains, structural collapse, and functional group decomposition, while also increasing energy consumption and production costs. Insufficient temperature or sintering time will result in incomplete reaction and insufficient modification, failing to achieve the expected material structure and performance.
[0044] Secondly, the present invention provides a single-crystal ternary cathode material, which is prepared by any one of the preparation methods described above.
[0045] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.
[0046] Preparation Example 1 The method for preparing modified cobalt hydroxyoxide in this preparation example is as follows: 1 g of cobalt hydroxyoxide (particle size 20 nm) was added to 8 mL of 90% ethanol aqueous solution, ultrasonically dispersed, 0.05 g of modified silane coupling agent was added, the mixture was stirred for 1 h, washed, and dried to obtain modified cobalt hydroxyoxide.
[0047] The preparation method of the modified silane coupling agent is as follows: 7.4 g glycidyl ether was added to a mixture of 21.9 g γ-isocyanate-propyltrimethoxysilane and 0.0295 g dibutyltin dilaurate, and the mixture was heated and stirred at 55 °C for 2 h to obtain a modified silane coupling agent.
[0048] Preparation Example 2 The method for preparing modified cobalt hydroxyoxide in this preparation example is as follows: 1 g of cobalt hydroxyoxide (particle size 20 nm) was added to 9 mL of 90% ethanol aqueous solution, ultrasonically dispersed, 0.07 g of modified silane coupling agent was added, the mixture was stirred for 1.5 h, washed, and dried to obtain modified cobalt hydroxyoxide.
[0049] The preparation method of the modified silane coupling agent is as follows: 7.4 g glycidyl ether was added to a mixture of 21.9 g γ-isocyanate-propyltrimethoxysilane and 0.0295 g dibutyltin dilaurate, and the mixture was heated and stirred at 55 °C for 2 h to obtain a modified silane coupling agent.
[0050] Preparation Example 3 The method for preparing modified cobalt hydroxyoxide in this preparation example is as follows: 1 g of cobalt hydroxyoxide (particle size 20 nm) was added to 10 mL of 90% ethanol aqueous solution, ultrasonically dispersed, 0.1 g of modified silane coupling agent was added, the mixture was stirred for 2 h, washed, and dried to obtain modified cobalt hydroxyoxide.
[0051] The preparation method of the modified silane coupling agent is as follows: 7.4 g glycidyl ether was added to a mixture of 21.9 g γ-isocyanate-propyltrimethoxysilane and 0.0295 g dibutyltin dilaurate, and the mixture was heated and stirred at 55 °C for 2 h to obtain a modified silane coupling agent.
[0052] Compare with Example 1 The only difference between this comparative example and preparation example 1 is that an equal amount of "KH-560" was used to replace the "modified silane coupling agent". The specific steps are as follows: 1 g of cobalt hydroxyoxide (particle size 20 nm) was added to 8 mL of 90% ethanol aqueous solution, ultrasonically dispersed, 0.05 g of KH-560 was added, the mixture was stirred and reacted for 1 h, washed, and dried to obtain modified cobalt hydroxyoxide.
[0053] Example 1 This embodiment provides a method for preparing a single-crystal ternary cathode material, including the following steps: S1, Ni, a ternary precursor material 0.65 Co 0.15 Mn 0.20 (OH)2, lithium source Li2CO3, and additive ZrO2 are mixed, with the molar ratio of Li ions to ternary precursor material being 1.02:1; the molar ratio of the additive to the ternary precursor material is 0.02:1. The mixture is first heated to 500℃ at 3℃ / min and sintered at a constant temperature for 2h; then heated to 900℃ at 2.5℃ / min and sintered at a constant temperature for 8h to obtain the first sintered product. S2. The primary sintering product, boric acid, and the modified cobalt hydroxyl oxide obtained in Preparation Example 1 were added to a 90% (v / v) ethanol aqueous solution and mixed. The amount of boric acid accounted for 0.05% of the mass of the primary sintering product, and the amount of modified cobalt hydroxyl oxide accounted for 0.3% of the mass of the primary sintering product. The mass ratio of the ethanol aqueous solution to the primary sintering product was 2:3. The mixture was ultrasonically dispersed, heated to 300℃ at 3℃ / min, and sintered at a constant temperature for 8 hours to obtain a single-crystal ternary cathode material.
[0054] Example 2 This embodiment provides a method for preparing a single-crystal ternary cathode material, including the following steps: S1, Ni, a ternary precursor material 0.65 Co 0.15 Mn 0.20 (OH)2, lithium source Li2CO3 and additive ZrO2 are mixed, with the molar ratio of Li ions to ternary precursor material being 1.04:1; the molar ratio of the additive to ternary precursor material is 0.04:1. The mixture is first heated to 560℃ at 4℃ / min and sintered at a constant temperature for 2h; then heated to 930℃ at 3℃ / min and sintered at a constant temperature for 9h to obtain the first sintered product. S2. The primary sintering product, boric acid, and the modified cobalt hydroxyl oxide obtained in Preparation Example 1 were added to a 90% (v / v) ethanol aqueous solution and mixed. The amount of boric acid accounted for 0.07% of the mass of the primary sintering product, and the amount of modified cobalt hydroxyl oxide accounted for 0.4% of the mass of the primary sintering product. The mass ratio of the ethanol aqueous solution to the primary sintering product was 2:3. The mixture was ultrasonically dispersed, heated to 400℃ at 3℃ / min, and sintered at a constant temperature for 9 hours to obtain a single-crystal ternary cathode material.
[0055] Example 3 This embodiment provides a method for preparing a single-crystal ternary cathode material, including the following steps: S1, Ni, a ternary precursor material 0.65 Co 0.15 Mn 0.20 (OH)2, lithium source Li2CO3 and additive ZrO2 are mixed, with the molar ratio of Li ions to ternary precursor material being 1.06:1; the molar ratio of the additive to ternary precursor material is 0.05:1. The mixture is first heated to 600℃ at 5℃ / min and sintered at a constant temperature for 2h; then heated to 950℃ at 3℃ / min and sintered at a constant temperature for 10h to obtain the first sintered product. S2. The primary sintering product, boric acid, and the modified cobalt hydroxyl oxide obtained in Preparation Example 1 were added to a 90% (v / v) ethanol aqueous solution and mixed. The amount of boric acid accounted for 0.1% of the mass of the primary sintering product, and the amount of modified cobalt hydroxyl oxide accounted for 0.5% of the mass of the primary sintering product. The mass ratio of the ethanol aqueous solution to the primary sintering product was 2:3. The mixture was ultrasonically dispersed, heated to 500℃ at 3℃ / min, and sintered at a constant temperature for 10h to obtain a single-crystal ternary cathode material.
[0056] Example 4 The only difference between this embodiment and Example 3 is that the modified cobalt hydroxyl oxide obtained in Example 1 is replaced with an equal amount of the modified cobalt hydroxyl oxide obtained in Example 2.
[0057] Example 5 The only difference between this embodiment and Example 3 is that the modified cobalt hydroxyl oxide obtained in Example 1 is replaced with an equal amount of the modified cobalt hydroxyl oxide obtained in Example 3.
[0058] Comparative Example 1 The only difference between this comparative example and Example 1 is that the "modified cobalt hydroxyoxide obtained in Preparation Example 1" is replaced with an equal amount of "modified cobalt hydroxyoxide obtained in Comparative Example 1".
[0059] Comparative Example 2 The only difference between this comparative example and Example 1 is that "cobalt hydroxyoxide (particle size of 20 nm)" was used to replace "the modified cobalt hydroxyoxide obtained in Preparation Example 1".
[0060] Comparative Example 3 The only difference between this comparative example and Example 1 is that boric acid is omitted. The specific steps are as follows: S1, Ni, a ternary precursor material 0.65 Co 0.15 Mn 0.20 (OH)2, lithium source Li2CO3, and additive ZrO2 are mixed, with the molar ratio of Li ions to ternary precursor material being 1.02:1; the molar ratio of the additive to the ternary precursor material is 0.02:1. The mixture is first heated to 500℃ at 3℃ / min and sintered at a constant temperature for 2h; then heated to 900℃ at 2.5℃ / min and sintered at a constant temperature for 8h to obtain the first sintered product. S2. The primary sintering product and the modified cobalt hydroxyoxide obtained in Preparation Example 1 were added to an ethanol aqueous solution with a volume fraction of 90% and mixed. The amount of modified cobalt hydroxyoxide accounted for 0.3% of the mass of the primary sintering product. The mixture was ultrasonically dispersed, heated to 300℃ at 3℃ / min, and sintered at a constant temperature for 8 hours to obtain a single-crystal ternary cathode material.
[0061] Comparative Example 4 The only difference between this comparative example and Example 1 is that the modified cobalt hydroxyl oxide is omitted. The specific steps are as follows: S1, Ni, a ternary precursor material 0.65 Co 0.15 Mn 0.20 (OH)2, lithium source Li2CO3, and additive ZrO2 are mixed, with the molar ratio of Li ions to ternary precursor material being 1.02:1; the molar ratio of the additive to the ternary precursor material is 0.02:1. The mixture is first heated to 500℃ at 3℃ / min and sintered at a constant temperature for 2h; then heated to 900℃ at 2.5℃ / min and sintered at a constant temperature for 8h to obtain the first sintered product. S2. The primary sintering product and boric acid are added to a 90% (v / v) ethanol aqueous solution and mixed. The amount of boric acid is 0.05% of the mass of the primary sintering product. The mixture is dispersed and heated to 300℃ at 3℃ / min. The mixture is then sintered at this temperature for 8 hours to obtain a single-crystal ternary cathode material.
[0062] Using the single-crystal ternary cathode material prepared in the examples and comparative examples as the cathode material, the cathode material was mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10. NMP (N-methylpyrrolidone) was added to form a uniform slurry, which was then coated onto copper foil, dried in an oven, and rolled under 10 MPa pressure to form circular electrode sheets with a diameter of 14 mm. Lithium-ion batteries were assembled according to industrial CR2025 button cell standards, using a Cellgard separator and a 1 mol / L LiPF6 solution with EC / PC / DEC as the electrolyte. The counter electrode was a lithium sheet. The entire assembly process was carried out in an argon-filled glove box, where the oxygen and moisture content were controlled below 0.5 ppm. The lithium-ion battery test conditions were as follows: temperature 25℃±1℃, charge-discharge cycle voltage range 3.0V-4.2V, current 0.1C (20mAh / g), and cycle test was performed for 100 cycles at 0.5C charge and 1C discharge. The test results are shown in Table 1.
[0063] Table 1
[0064] As can be seen from Table 1, the rate discharge capacity and cycle performance of the batteries prepared in Examples 1-5 are better than those of Comparative Examples 1-4.
[0065] Compared with Example 1, Comparative Example 1 omitted the urethane group, and the performance was lower than that of Example 1. This shows that the carbonyl oxygen and amino nitrogen in the urethane group can act as dual coordination sites to form a stable chelate structure with lithium ions, build a low-impedance lithium ion fast transport channel at the interface, and reduce interface polarization.
[0066] Compared to Example 1, Comparative Example 2, which directly used unmodified cobalt hydroxyl oxide, showed a decrease in performance. This indicates that the epoxy group can undergo a ring-opening addition reaction with boric acid, significantly enhancing the binding force between the two coating components. This allows the coating layer to remain intact during long-term charge-discharge processes, significantly improving cycle stability. Simultaneously, the carbonyl oxygen and amino nitrogen in the urethane group can act as dual coordination sites to form a stable chelate structure with lithium ions, constructing a low-impedance lithium-ion fast transport channel at the interface and reducing interfacial polarization. The synergistic effect of these two factors ensures the long-term stability of the interfacial structure through chemical bonding and optimizes lithium-ion migration kinetics through coordination, thereby achieving a simultaneous improvement in cycle life and rate performance.
[0067] Compared with Example 1, Comparative Examples 3 and 4 omitted boric acid and modified cobalt hydroxyl oxide, respectively. The performance of both examples decreased compared with Example 1. This indicates that, on the one hand, the glassy coating layer formed by boric acid can effectively isolate the material from the electrolyte, suppress the occurrence of side reactions, and improve the interfacial stability of the material; on the other hand, modified cobalt hydroxyl oxide can regulate the morphology and grain growth of single crystals, regulate the morphology and grain size of single crystal particles, improve crystallinity and structural integrity, reduce lattice distortion and defects, reduce the lattice impedance of lithium-ion transport, and effectively improve the ionic conductivity and rate performance of the material. The synergistic effect of the two can optimize the crystal structure integrity, interfacial stability and ion transport performance of the material, and finally obtain a single-crystal ternary cathode material with excellent electrochemical performance, cycle stability and safety.
[0068] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.
Claims
1. A method for preparing a single-crystal ternary cathode material, characterized in that, Includes the following steps: S1. The ternary precursor material, lithium source and additives are mixed and sintered for the first time to obtain the first sintered product. S2. The primary sintering product, along with boric acid and modified cobalt hydroxyl oxide, are added to an organic solvent, mixed, ultrasonically dispersed, and then sintered a second time to obtain a single-crystal ternary cathode material.
2. The method for preparing the single-crystal ternary cathode material according to claim 1, characterized in that, In step S1, the molar ratio of Li ions to ternary precursor material is (1.02-1.06):1; the molar ratio of additive to ternary precursor material is (0.02-0.05):
1.
3. The method for preparing the single-crystal ternary cathode material according to claim 1, characterized in that, In step S1, the ternary precursor material is Ni. 0.65 Co 0.15 Mn 0.20 (OH)2; The lithium source is Li2CO3; The additives include any one or more of ZrO2, Al2O3 and Y2O3; The first sintering process involves raising the temperature to 500-600℃ at a rate of 3-5℃ / min and sintering at a constant temperature for 2 hours; then raising the temperature to 900-950℃ at a rate of 2.5-3℃ / min and sintering at a constant temperature for 8-10 hours.
4. The method for preparing the single-crystal ternary cathode material according to claim 1, characterized in that, In step S2, the amount of boric acid used accounts for 0.05%-0.1% of the mass of the primary sintering product; The amount of modified cobalt hydroxyoxide used accounts for 0.3%-0.5% of the mass of the primary sintering product; The organic solvent is an aqueous ethanol solution with a volume fraction of 90%, and the mass ratio of the organic solvent to the primary sintering product is 2:
3.
5. The method for preparing the single-crystal ternary cathode material according to claim 1, characterized in that, In step S2, the method for preparing the modified cobalt hydroxyl oxide is as follows: Cobalt hydroxyoxide was added to an aqueous ethanol solution, ultrasonically dispersed, a modified silane coupling agent was added, the mixture was stirred, washed, and dried to obtain modified cobalt hydroxyoxide.
6. The method for preparing the single-crystal ternary cathode material according to claim 5, characterized in that, The ratio of cobalt hydroxyoxide, ethanol aqueous solution, and modified silane coupling agent is 1g:8-10mL:0.05-0.1g; the volume fraction of the ethanol aqueous solution is 90%. The stirring reaction time is 1-2 hours; The cobalt hydroxyoxide has a particle size of 10-40 nm.
7. The method for preparing the single-crystal ternary cathode material according to claim 5, characterized in that, The modified silane coupling agent is prepared by: Glycidyl ether was added to a mixture of γ-isocyanate-propyltrimethoxysilane and dibutyltin dilaurate, and the mixture was heated and stirred to obtain a modified silane coupling agent.
8. The method for preparing single-crystal ternary cathode material according to claim 7, characterized in that, The mass ratio of glycidyl ether, γ-isocyanate-propyltrimethoxysilane, and dibutyltin dilaurate is 7.4:21.9:0.0295. The heating and stirring reaction is carried out at a temperature of 50-60℃ for 1-2 hours.
9. The method for preparing the single-crystal ternary cathode material according to claim 1, characterized in that, In step S2, the secondary sintering is carried out at a rate of 3℃ / min to 300℃-500℃, and then sintered at a constant temperature for 8-10 hours.
10. A single-crystal ternary cathode material, characterized in that, It is prepared by the preparation method according to any one of claims 1-9.